2019
DOI: 10.1016/j.jnutbio.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-dependent effects of cis-9,trans-11- and trans-10,cis-12-CLA isomers on glucose and lipid metabolism in adult male mice

Abstract: Mixtures of the two major conjugated linoleic acid (CLA) isomers trans-10,cis-12-CLA and cis-9,trans-11-CLA are used as over the counter supplements for weight loss. Because of the reported adverse effects of CLA on insulin sensitivity in some mouse studies, we sought to compare the impact of dietary t10c12-CLA and c9t11-CLA on liver, adipose tissue, and systemic metabolism of adult lean mice. We fed 8 week-old C57Bl/6J male mice with low fat diets (10.5% Kcal from fat) containing 0.8% t10c12-CLA or c9t11-CLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It should be noted that the delipidation effect of t10,c12-CLA on adipose tissue and the adipose tissue-dependent effect induced by t10,c12-CLA was fully investigated by previous studies. However, several studies also found that the antiobesity effect of t10,c12-CLA might promote fatty liver by enhancing fatty acid transport to the liver ( Clement et al., 2002 ; Vyas et al., 2012 ; Cordoba-Chacon et al., 2019 ). Interestingly, these findings were closely associated with the animal models used.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the delipidation effect of t10,c12-CLA on adipose tissue and the adipose tissue-dependent effect induced by t10,c12-CLA was fully investigated by previous studies. However, several studies also found that the antiobesity effect of t10,c12-CLA might promote fatty liver by enhancing fatty acid transport to the liver ( Clement et al., 2002 ; Vyas et al., 2012 ; Cordoba-Chacon et al., 2019 ). Interestingly, these findings were closely associated with the animal models used.…”
Section: Discussionmentioning
confidence: 99%
“…To assess hepatic fatty acid composition, total lipids were extracted using the Bligh and Dyer method [30]. An aliquot of extracted lipids was transmethylated with BF3-methanol (Sigma-Aldrich) to quantify specific methyl esters of fatty acids using GC/MS, as we previously reported [31,32], using 17 : 1 as the internal standard to quantify the amount of each fatty acid in the sample. In addition, we used a commercial sample of polyunsaturated fatty acid mixture (PUFA-2, Supelco) to identify the different fatty acids in the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on mice have yielded conflicting results on whether dietary t10c12-CLA leads to hepatic steatosis [15,[29][30][31]. The current observation of fatty liver and hypertriglyceridemia in pai/pai mice, which may be associated with t10c12-CLAinduced excess corticosterone for the overproduction of corticosterone can lead to Cushing syndrome, corticosteroid-induced lipodystrophy, hypertriglyceridemia, or hepatic steatosis [32,33].…”
Section: Discussionmentioning
confidence: 91%